Monitoring financial stability risks of South African collective investment schemes - Detering, Kirstin (School of Economics, 2022)
Financial stability and systemic risk have been central to macroeconomic policy since the Global Financial Crisis (GFC) of 2007/2008. Whereas the regulatory focus previous to the crisis was on micro-prudential risk management of the formal banking sector, policymakers and supervisors realized that macro-prudential oversight of the financial system, including Non-Bank Financial Intermediaries, is key to maintaining financial stability. Since Collective Investment Schemes (CISs) present a large component of South African Non-Bank Financial Intermediation (NBFI), this paper proposes measures to monitor risks within this sector based on the indicators applied by the Financial Stability Board (FSB) in its Global Monitoring Report on Non-Bank Financial Intermediation as well as other financial stability reports. All measures are calculated on a quarterly basis and we find that the results for the FSB indicators are comparable to the findings in the Global Monitoring Report on Non-Bank Financial Intermediation. This implies that the levels of Liquidity Transformation (LT) are in the upper bound, which is characteristic of EMEs. For Money Market Funds, the levels of LT seem to be slightly problematic as their Weighted Average Maturity surpasses the regulatory threshold of 130 days in all but two quarters which raises concerns about the liquidity status of these funds and how they would fair in circumstances of economic distress.